2022
DOI: 10.1177/00219096221111359
|View full text |Cite
|
Sign up to set email alerts
|

Is It Really Feminization of Agriculture? The Issue of Household Food Security in Lesotho’s Southern Lowland District

Abstract: The study assessed the roles of women and the ownership of land trends in Lesotho, particularly during the 2015/2016 drought in Lesotho. A mixed-method approach, which combined both qualitative and quantitative research approaches, and a semi-structured questionnaire was used to collect data. The collected data included demographic information, household assets, gender roles in agricultural activities, and decision-making in the household to explore feminization of agriculture and its impact on household food … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A study revealed that 14% of the population in Lesotho faces food insecurity (FAO, 2023). The occurrence of droughts and floods, insufficient agricultural techniques, high food prices, and global economic downturns have worsened food insecurity in the Southern Africa Developing Community (SADC) region, including Lesotho (Mokati et al, 2022).…”
Section: The Contribution Of Livestock To Food Securitymentioning
confidence: 99%
“…A study revealed that 14% of the population in Lesotho faces food insecurity (FAO, 2023). The occurrence of droughts and floods, insufficient agricultural techniques, high food prices, and global economic downturns have worsened food insecurity in the Southern Africa Developing Community (SADC) region, including Lesotho (Mokati et al, 2022).…”
Section: The Contribution Of Livestock To Food Securitymentioning
confidence: 99%
“…A substantial body of evidence indicates that women run less than 25% of agricultural businesses in developing nations. Moreover, "women in the developing world are five times less likely than men to own land, and [if they do] their farms are often smaller and less fertile" (Doss et al, 2015;Mokati et al, 2022). In this context, Agarwal (2018) argues that uneven access to ownership of land in rural areas, which is mandated by patriarchal-oriented customary norms, has resulted in low agricultural production and ongoing food insecurity in many households on the African continent.…”
Section: Introductionmentioning
confidence: 99%